2021
DOI: 10.3390/ijerph18084166
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Apoptotic Activity of Artichoke Leaf Extracts in Human HT-29 and RKO Colon Cancer Cells

Abstract: (1) Background: Cynara cardunculus L. subsp. scolymus (L.) Hegi, popularly known as artichoke, is an herbaceous plant belonging to the Asteraceae family. Artichoke leaf extracts (ALEs) have been widely used in traditional medicine because of their hepatoprotective, cholagogic, hypoglycaemic, hypolipemic and antibacterial properties. ALEs are also recognized for their antioxidative and anti-inflammatory activities. In this study, we evaluated the cytotoxic, genotoxic, and apoptotic activities, as well as effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Human colorectal adenocarcinoma Caco-2 and HT-29 cells were cultured as previously reported [ 28 , 53 ]. HMC-1.2 cells (HMC-1.2, Merck-Millipore, Darmstadt, Germany) were plated at 2.5 × 10 5 cells/mL density in T25 flasks with Isove Medium, 1.2 mM α-thioglycerol (Sigma Cat No.…”
Section: Methodsmentioning
confidence: 99%
“…Human colorectal adenocarcinoma Caco-2 and HT-29 cells were cultured as previously reported [ 28 , 53 ]. HMC-1.2 cells (HMC-1.2, Merck-Millipore, Darmstadt, Germany) were plated at 2.5 × 10 5 cells/mL density in T25 flasks with Isove Medium, 1.2 mM α-thioglycerol (Sigma Cat No.…”
Section: Methodsmentioning
confidence: 99%
“…1 ) was synthesised in the laboratory of Professor Claudio Santi as previously described [ 16 ] by refluxing equimolar amounts of PhSeCl and freshly activated zinc in dry THF. The top concentration used was the highest soluble concentration obtained—as previously described [ 22 ]—according to the US National Toxicology Program Interagency Center for the Evaluation of Alternative Toxicological Methods (NICEATM) [ 23 ] and abiding by the US Food and Drug Administration [ 24 ] and OECD guidelines for testing pharmaceuticals intended for human use [ 25 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Artichoke bioactive constituents have antibacterial, anti-malarian, antiviral (Hep C virus), anti-inflammatory, antioxidative, hepatoprotective, and metabolic effects ( Ben Salem et al, 2015 ; Elsebai et al, 2016 ; Villarini et al, 2021 ) ( Table 3 ). Constituents isolated from artichoke (e.g., cynaropicrin) are involved in the regulation of the NF-κB pathway and downregulate inflammatory cytokines ( Elsebai et al, 2016 ).…”
Section: Artichokementioning
confidence: 99%
“…The treatment of volunteers with total plasma cholesterol levels 6.0–8.0 mmol/l with artichoke leaf extract (ALE) significantly decreased total cholesterol levels, but not low-density lipoprotein and high-density lipoprotein ( Bundy et al, 2008 ). An in vitro study demonstrated that treatment of HT-29 and RKO tumor cells with cynaropicrin, caffeoylquinic acids, and chlorogenic acid-induced cell apoptosis suggests that ALEs could be potentially used as an effective tool chemotherapeutic agent ( Villarini et al, 2021 ) ( Table 3 ).…”
Section: Artichokementioning
confidence: 99%